Actividad reproductiva de tres cultivares de soya, por sección de la planta y estadios de desarrollo - Marchezan, E; Costa, J.A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Caracterization of the reproductive activity of soybean cultivars Planalto, Br-4 and Salina, was performed by node, both for the main stein and branches. Condition for high yield was provided. This field experiment was conducted at the Estacilo Experimental Agronomica da Universidade Federal do Rio Grande do Sul, during 1980181. The medium part contributed, approximately, with 50% of the flowers and pods pro-duced and fired. About 50% of the reproductive structures produced by the branches were on those located at the lower part of the twin stem, and the other half on branches originated on the medium section of the plant. On the average, the time during which the reproductive structures were produced was of 53 days (from R1 until the beginning of R6) About 50% of the flowers were produced during the first two weeks of flowering. The rate of flower production picked up between days seventh and tenth after the beginning of the flowering period.